Adapting to Change: The Continuous Development of Business and Management Education - Alimaningtyas, Deni; Ghozali, Mohammad Syukri; Wardana, Ludi Vishnu; Murwani, F. Danardana; Wati, Andy Prasetyo (PT FORMOSA CENDEKIA GLOBAL, 2024)
Business and management education continues to experience dynamic development in line with continuous changes in the global business world. This research analyzes the factors driving change in business education, including technological advances, changing business paradigms, and the need for new skills in the digital era. This research uses the Systematic Literature Review (SLR) method by collecting and analyzing journals related to keywords. Based on the literature study conducted, it was found that the role important in teaching skills, knowledge, and understanding required for success in the continuous business world changed. Besides that education in the field of business also prepares individuals To face challenges and complex and ongoing market dynamics, thus increasing opportunity success and contribution positively in organizations and society. Thus, deepening studies in the field of business and management Not only gives superiority but also possible for individuals to become agents of adaptive and proactive change in facing changes that occur in a way Keep going continuously.